The prince and the porker - Bently, Peter 1960- (Andersen Press, 2015)
Pignatius was passing the palace one day, when he saw ten fresh buns left to cool on a tray ... Sneaking into the palace, looking for more treats, Pignatius tries on a wig and some clothes and the servants mistake him for the real prince! Of course the rein of this porky impostor can't last long, but when the actual prince returns, he saves Pignatius's bacon. It turns out that he's always wanted a double to deal with a particularly frightening dragon - his Aunt Alice!